2021
DOI: 10.1038/s41598-021-90436-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of considerable C and N transfer from peas to cereals via direct root contact but not via mycorrhiza

Abstract: Intercropping of legumes and cereals is an important management method for improving yield stability, especially in organic farming systems. However, knowledge is restricted on the relevance of different nutrient transfer pathways. The objective of the study was to quantify nitrogen (N) and carbon (C) transfer from peas to triticale by (1) direct root contact (= R), (2) arbuscular mycorrhizal fungi (AMF; = A), and (3) diffusion (= D). Pea (Pisum sativum cv. Frisson and P2) and triticale (Triticum × Secale cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…In this experiment, the NTA from soybean to cotton increased with the weakening of the root barrier, due to the larger contact areas of root between the species. A main reason for the high NTA of direct root contact was resource complementarity between nonlegumes and legumes, which promotes interspecific N uptake directly by specific root exudates or indirectly by induced microbial activity 47‐49 . Notably, this study showed that the cotton with the NB treatment had greater RDWD, RLD, and root angle than with the CB and SB treatments, which promoted absorption and transfer of soil moisture and nutrients 50 …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this experiment, the NTA from soybean to cotton increased with the weakening of the root barrier, due to the larger contact areas of root between the species. A main reason for the high NTA of direct root contact was resource complementarity between nonlegumes and legumes, which promotes interspecific N uptake directly by specific root exudates or indirectly by induced microbial activity 47‐49 . Notably, this study showed that the cotton with the NB treatment had greater RDWD, RLD, and root angle than with the CB and SB treatments, which promoted absorption and transfer of soil moisture and nutrients 50 …”
Section: Discussionmentioning
confidence: 71%
“…A main reason for the high NTA of direct root contact was resource complementarity between nonlegumes and legumes, which promotes interspecific N uptake directly by specific root exudates or indirectly by induced microbial activity. [47][48][49] Notably, this study showed that the cotton with the NB treatment had greater RDWD, RLD, and root angle than with the CB and SB treatments, which promoted absorption and transfer of soil moisture and nutrients. 50 In this experiment, we found that, although the growth of soybean root was negatively correlated with the NTA treatment, the size of the effect of NTA on soybean was greater than its effect on cotton, mainly because soybean had more powerful lateral roots to regulate the soil environment.…”
Section: Effects Of Root Barrier Treatments On Root Distribution With...mentioning
confidence: 66%
“…The competition for N among species was weakened under higher soil N, with plants meeting their own growth without relying on N transfer (Yong et al, 2015). Generally, the absorption capacity of N of legumes was weaker than that of associated crops, while the roots of legumes decompose faster because of the low C/N ratio (Hupe et al, 2021). Therefore, the root turnover of legumes in the intercropping system provides a pathway for N transfer.…”
Section: Effects Of N Fertilizer Rates On Productivity and N Uptake U...mentioning
confidence: 99%
“…Studies on intercropping systems suggest that plants may acquire N directly from companion plants through in-season N transfer (Johansen & Jensen, 1996). In a recent study, Hupe et al (2021) reported that direct root contact resulted in high pea rhizodeposition, and thus the large amount of N transfer to triticale (×Triticosecale Wittm. ex A. Camus).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Hupe et al. (2021) reported that direct root contact resulted in high pea rhizodeposition, and thus the large amount of N transfer to triticale ( ×Triticosecale Wittm . ex A. Camus).…”
Section: Introductionmentioning
confidence: 99%